IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) OLEH PEMERINTAH DAERAH DAN SEKOLAH MENENGAH PERTAMA (Studi Kasus: Kecamatan Tabanan, Kabupaten Tabanan, Provinsi Bali) - Natalia Krisdayanti, Desy (CITIZEN CHARTER, 2014)
ABSTRAC Â  Education is a basic human need to live and achieve a better life. One effort to meet the educational needs made ??the Law Number 20 Year 2003 on National Education System which mandates every citizen aged 7-15 years of compulsory basic education. To further the success of compulsory education and also to reduce the burden of the cost of education, then the government provide School Operational Assistance. The porpose of this research are to know how the implementation BOS by local goverment and junior high school then what the aspec which influence implementation of this policy. We choose Tabanan Regency to be research area with the sample SMP 1 and SMPN5 Tabanan to see how the implementation of BOS fund in there, because Tabanan is one of the regencies with the lowest matching BOS fund. This study used a qualitative research method of collecting information using in-depth interview, observasi non partisifan and documentation techniques. According to the theory of Edward III, there are four aspects that affect the implementation of BOS fund: communication, resources (human and financial), attitudes and bureaucratic structures. On the four aspects of the synergy between local goverment and junior high schools are not good, so they must reform and make good governance in education policy. Â  Key Words : Public Policy, Education, School Operational Assistance